Red blood cell genotyping in China. (June 2016) - Ji, Y. L.; van der Schoot, C. E.
Abstract : The common antigens of ABO, Rh, MNS, Duffy, Kidd, Diego, Yt and Dombrock blood group systems have a polymorphic distribution in the Chinese population. The Mur antigen and anti‐Mur are more common in the Chinese Han and some minority groups in the southern region of China. Except for the common ABO alleles ( A101, A102, B101, O01 and O02 ), more than 100 new alleles have been reported in the Chinese population, in which the effect of many critical mutations on the variant expression of A and B antigens still needs to be investigated. For RHD genotyping, only 6% of Chinese D+ people were heterozygous for the RHD gene with Dd genotype. Compared with the complete deletion of the RHD gene accounting for D‐ phenotype in the Caucasian population, 20–40% of the Chinese individuals with D‐ phenotype carry RHD variant alleles. Among them, 'Asian type' DEL allele ( RHD*DEL1 defined by 1227G>A, Lys409Lys) is the most common variant and is classified as D‐, and it can only be identified by absorption/elution testing, which is not routinely conducted. Several studies indicated that the Chinese pregnant women with 'Asian type' DEL allele were not immunized by the incompatible pregnancy, which suggested that the 'Asian type' DEL recipient could receive D+ blood safely. Weak D type 15 and DVI type 3 are the most common RHD variant alleles, accounting for more than 70% of RhD variants in the Chinese population. In addition, the genotyping analysis for the rare null phenotypes, including the para‐Bombay, Jk(a‐b‐), Lu(a‐b‐), p, Rhnull and KELnull phenotypes, are also summarized.